2010
DOI: 10.1103/physrevb.82.064424
|View full text |Cite
|
Sign up to set email alerts
|

Cupric chlorideCuCl2as anS=12chain multiferroic

Abstract: Magnetoelectric properties were investigated for an S = 1/2 chain antiferromagnet CuCl2, which turns out to be the first example of non-chalcogen based spiral-spin induced multiferroics. Upon the onset of helimagnetic order propagating along the b-axis under zero magnetic field (H), we found emergence of ferroelectric polarization along the c-axis. Application of H along the b-axis leads to spin-flop transition coupled with drastic suppression of ferroelectricity, and rotation of H around the b-axis induces th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
65
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 41 publications
14
65
4
Order By: Relevance
“…This mechanism, which is known as a KNB mechanism, 6 is realized in several one-dimensional magnetic materials. [11][12][13][14][15][16][17][18][19][20][21] In our model, however, we have to impose a restriction in order to preserve integrability. While the standard model to describe the MEE in one-dimensional magnetic materials with the KNB mechanism is the J 1 -J 2 chain, Eq.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This mechanism, which is known as a KNB mechanism, 6 is realized in several one-dimensional magnetic materials. [11][12][13][14][15][16][17][18][19][20][21] In our model, however, we have to impose a restriction in order to preserve integrability. While the standard model to describe the MEE in one-dimensional magnetic materials with the KNB mechanism is the J 1 -J 2 chain, Eq.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] In turn, the discovery of the deep relationship between magnetic structure and ferroelectricity in several spin-chain materials stimulated further research of multiferroics and paved a way between the physics of multiferroics and quantum spin systems. The simplest system exhibiting the MEE by means of KNB mechanism, considered so far, is the S = 1/2 J 1 -J 2 -spin chain, which is believed to be a more or less adequate model for several multiferroic materials such as LiCu 2 O 2 , [15][16][17] LiCuVO 4 , [18][19][20] CuCl 2 , 21 and others. The expression for the electric polarization becomes particularly simple in the case of a one-dimensional linear chain, say, in the x direction.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that, for example, in TbMnO 3 [24] and MnWO 4 [25] two different order parameters condense successively, whereas in CuCl 2 [21,28] they condense simultaneously. These order parameters transform according to different irreducible representations of the crystal space group.…”
Section: Introductionmentioning
confidence: 99%
“…4 Not only oxide compounds but also a halide CuCl 2 with quasi-one-dimensional Cu-Cl network were reported to undergo a ferroelectric transition. 38) In frustrated spin systems, non-trivial types of magnetic order such as a helix, spin density wave, cone, and fan often emerge. In any case, all the major exchange interactions between adjacent magnetic moments cannot be minimized in energy.…”
Section: Frustrated Spin Systems As a Source Of Ferroelectricitymentioning
confidence: 99%